Checklist of Molluscs in Nallavadu Lagoon, Puducherry, India - Padmavathy, A.; Anbarashan, M. (Our Nature, 2011)
The molluscs constitute a natural resource of sizable magnitude in many parts of the world. They are an age old group represented among the early fossils, a group of great diversity in size, distribution, habitat and utility. This paper presents checklist of molluscs from Nallavadu Lagoon, Puducherry, India. A total of 15 molluscs, nine species of Gastropods (6 families) and 6 species of Bivalves (4 families) were recorded. DOI: 10.3126/on.v8i1.4343